Voice Analysis of Cancer Experiences Among Patients With Breast Cancer: VOICE-BC. (October 2021) - Law, Ernest H; Auil, Maria J; Spears, Patricia A; Berg, Kiersten; Winnette, Randall
Patient experience literature in early-stage breast cancer (eBC) is limited. This study used a mixed-methods approach to examine patient conversations from public online forums to identify and evaluate eBC-related themes. Among 60, 000 eBC-related posts published September 2014–2019, text from a random subset of 15, 000 posts was extracted and grouped into linguistically similar, mutually exclusive clusters using an advanced natural language processing (NLP) algorithm. Clusters were characterized using four quantitative metrics: betweenness centrality (linguistic similarity to other areas of the cluster network), sentiment (general attitude toward a topic), recency (average date of posts), and volume (total number of posts). This analysis represented 3906 unique users (67% and 33% obtained from cancer–specific and general health/nonhealth forums, respectively). Of the 27 clusters identified, most important were "discussing recurrence & progression, " "understanding diagnosis & prognosis, " and "understanding cancer, biomarkers, and treatments." Several major themes related to recurrence risk, diagnosis, monitoring, and treatment were identified. Additional emphasis on communicating the disease recurrence risk and shared decision-making could strengthen patient-clinician partnerships.